(untitled) (International Journal of Innovative Research in Engineering & Management, 2023)
Concrete is the universally accepted material for its adverse properties with high usage of the concrete for all type of the works in the world, it leads to depletion of natural resources like river sand, and granite. Which are the components of the concrete as fine aggregate and coarse aggregate in this project M30 grade concrete is taken in which 10%,20%&30% of coarse aggregate is replaced with over burnt bricks and 10%,20%and 30% of coarse aggregate replaced with pumice by volume. And the compressive, flexural and split tensile strength properties at 7,28& 56 days and the unit weights of the concrete compared. In order to safe guard the natural resources, alternate material like over burnt bricks, pumice considered in the present project.